The dispute over classical sociobiology - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2020)
“Sociobiology: New Synthesis” is a book written by W. O. Wilson, which in l975 started the famous dispute over sociobiology. The dispute is the contemporary version of the old one about the nature of man. The issue concerns the factor, which determines the behaviours of living organisms, especially human beings. Two groups took part in that dispute. On one side, there were sociobiologists under the leadership of Wilson. On other, there were left-wing scientists and students connected with Sociobiology Study Group of Science for the People. In the first stage, the dispute was very intense and political, however, it soon became more content-related. The dispute is not over yet. Both sides agreed to a ceasefire, but they are ready to open it at any time.